Efeitos da ingestão aguda do suco de laranja na resposta glicêmica e insulínica, níveis séricos de leptina e adiponectina, consumo energético e atividade antioxidante - Paiva, Aline Cardoso de [UNESP] (2014)
Introduction: Orange juice contains sugars and flavonoids that may influence satiety and energy and macronutrient intake, and body weight. Objective: investigating the effect of acute ingestion of fresh orange juice and pasteurized whole juice on blood glucose, markers of satiety and food intake in normal weight and overweight. Methods: A clinical study with acute dietary intervention in 36 healthy subjects with adequate nutritional status or overweight of both sexes was conducted. The subjects underwent three experimental steps: 1) intake of fresh orange (FOJ), 2) ingestion of pasteurized juice (POJ) and orange juice, 3) ingestion of the control beverage (CB) with orange flavor. Before and after consumption of the test beverage, bloods sampling (0, 30, 60, 120 and 300 min) were taken for analysis of biochemical parameters (glucose, insulin, leptin, adiponectin) and subsequent calculation of insulin resistance. Soon after ingestion of drinks volunteers received a breakfast of ad libitum where food consumption were noted in this meal and also the other made during the experimental day. Analyses of body composition (weight, height, body mass index, body fat percentage and waist circumference), parameters metabolic (total cholesterol, LDL-C, HDL-C, triglycerides) were performed on the first day of the study. Hormones (leptin and adiponectin) were measured by ELISA. Oxidative stress was quantified by measuring TBARS and ABTS methods. Results: The results showed that obese of both sexes volunteers have risk factors for developing metabolic syndrome, 61% have insulin resistance. For normal weight subjects, total concentration (AUC300min) of glucose and insulin was higher after CB, following by POJ (intermediate), and FOJ (lower). By it turn, normal weight subjects have shown total concentration of leptin (AUC300min) higher after FOJ intake, middle after POJ, and lower after CB. Adiponectin levels showed no change compared to the tested beverages.